2019
DOI: 10.5093/jwop2019a12
|View full text |Cite
|
Sign up to set email alerts
|

Affective Commitment, Participative Leadership, and Employee Innovation: A Multilevel Investigation

Abstract: Organizations have increasingly recognized that employee innovation-defined as the intentional generation, promotion, and implementation of new and useful ideas aimed at benefiting role performance, the group, or the organization (West & Farr, 1990)-is a critical resource for ensuring effectiveness, growth, and continuous development in rapidly changing and uncertain environments (Hammond, Neff, Farr, Schwall, & Zhao, 2011). Employee innovation entails in-role and extra-role components (Poto nik & Anderson, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 70 publications
4
76
0
4
Order By: Relevance
“…This finding is also consistent with the reciprocity norm in social exchange theory. Further, our results support the empirical findings of very recent leadership studies on employee outcomes, such as inclusive leadership on employee innovative behavior [34], paternalistic leadership on innovative behavior [35], leadership on commitment and innovative work behavior [33], and team-level participative leadership on employee innovation [53]. Two recent studies have also indicated the significant effects of transformational leadership on innovation in the public sector of three different countries (Denmark, the Netherlands, and Spain) [76] and leader inclusiveness on work-unit performance in hospitals [77].…”
Section: Evaluation Of the Findings And Theoretical Implicationssupporting
confidence: 87%
See 2 more Smart Citations
“…This finding is also consistent with the reciprocity norm in social exchange theory. Further, our results support the empirical findings of very recent leadership studies on employee outcomes, such as inclusive leadership on employee innovative behavior [34], paternalistic leadership on innovative behavior [35], leadership on commitment and innovative work behavior [33], and team-level participative leadership on employee innovation [53]. Two recent studies have also indicated the significant effects of transformational leadership on innovation in the public sector of three different countries (Denmark, the Netherlands, and Spain) [76] and leader inclusiveness on work-unit performance in hospitals [77].…”
Section: Evaluation Of the Findings And Theoretical Implicationssupporting
confidence: 87%
“…Study has actually discovered that comprehensive leadership has a significant impact on employee innovation [34]. More recently, employee commitment has been discovered to be an antecedent of SIB in companies [53].…”
Section: Employee Engagement In Creative Work Tasks and Service Innovmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample frame of the study consists of manufacturing, processing, designing, engineering, marketing, and product development departments as researchers have suggested that employees' innovative work behavior is pertinent to these departments. [147][148][149] Data was collected over the two periods of time so as to minimize the effects of common method bias. 150,151 Both of the surveys were properly coded so that they could be matched and supervisorsubordinate dyads could be formed.…”
Section: Sample Design and The Data Collectionmentioning
confidence: 99%
“…[13,14] A very prominent management style demonstrated that it could improve motivation through participatory leadership style. [15][16][17][18] And a project manager could use power or different leadership styles to inspire his team. Fourthly, we valued the art of team management.…”
Section: Discussionmentioning
confidence: 99%